2010
DOI: 10.1177/0891988710373597
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Education Level and Mini-Mental State Examination Domains Among Older Mexican Americans

Abstract: To study the effect of education on the performance in the Mini-Mental State Examination (MMSE) domains, we included 2,861 Mexican Americans aged 65 and older from the Hispanic Established Populations for Epidemiologic Studies of the Elderly (EPESE) followed from 1993-1994 until 2004-2005. The MMSE was examined as total score (0-30) or divided in two global domains: 1) no-memory (score 0-24): Orientation, attention, and language; and 2) memory (score 0-6): working and delayed memory. Mean age and total MMSE we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
70
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(80 citation statements)
references
References 53 publications
9
70
0
1
Order By: Relevance
“…Along with most of the previous studies conducted with the MMSE (Anderson et al, 2007;Bravo & Hébert, 1997;Matallana et al, 2011), our results show that educational level is the variable that most significantly contributed to the prediction of the MMSE scores, followed by age. Together, these variables explained 26% of the results variance; therefore, as in previous Portuguese studies (Guerreiro et al, 1994;Guerreiro, 1998;Morgado et al, 2009) and in most of the international normative studies, these variables were the optimal criteria for the establishment of MMSE normative data for the Portuguese population.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Along with most of the previous studies conducted with the MMSE (Anderson et al, 2007;Bravo & Hébert, 1997;Matallana et al, 2011), our results show that educational level is the variable that most significantly contributed to the prediction of the MMSE scores, followed by age. Together, these variables explained 26% of the results variance; therefore, as in previous Portuguese studies (Guerreiro et al, 1994;Guerreiro, 1998;Morgado et al, 2009) and in most of the international normative studies, these variables were the optimal criteria for the establishment of MMSE normative data for the Portuguese population.…”
Section: Discussionsupporting
confidence: 82%
“…Older age has been found to significantly increase the probability of obtaining lower scores, whereas the worst performance has been found among those with lower education levels, and ceiling effects have been observed among highly educated individuals (Anderson, Sachdev, Brodaty, Trollor, & Andrews, 2007;Bravo & Hébert, 1997;Gallacher et al, 1999;Matallana et al, 2011;Moraes, Pinto, Lopes, Litvoc, & Bottino, 2010). The magnitude of the effect of education level is so strong that the education is invariably considered a criterion for the establishment of normative-data for the MMSE (Han et al, 2008;Mathuranath et al, 2007;Measso et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Our study observed that subjects who achieved secondary and tertiary education had lower risk of cognitive impairment. This finding is consistent with a number of other studies which showed that people with primary school education had higher risk to develop cognitive impairment 18,19 . This implies that every country should take appropriate measures to prevent school drop-outs and promote higher education by providing free education at least up to secondary level.…”
Section: Based On the Logistic Regression Shown Insupporting
confidence: 93%
“…Because of the cultural background, more than 50% of the participants had less than 6 years of formal education. Cultural background had an influence on MMSE performance, and education is closely related to cultural background 22. MMSE scores generally decline with advancing age and can be biased by baseline educational level and language 23.…”
Section: Discussionmentioning
confidence: 99%